Design and implementation of labview based bore well child rescue robot - Sujatha, M; Prabakaran, N; R, Selvakumar (International Journal of Engineering and Technology, 2017)
An innovative method is proposed for rescuing a child from a borehole and to keep the child in conscious state. Children accidentally fall into the borehole which yielded water and subsequently left uncovered. A suitably strong cap of bright color to cover the mouth of the borehole will avoid such accidents. It is difficult and also risky process to rescue the trapped child after fallen into the borehole. In this paper, a robot is designed in such a way that it handles the trapped child carefully and monitors the child continuously. The robot structure consists of power supply, gear motors, oxygen concentrator, camera and micro controller, robotic arms, temperature sensor, audio player which has parents voice, heart beat monitoring system, lifting rods, servo motors. The condition of the child is captured with CCTV camera and monitored on a TV.The proposed system is implemented using NI LabVIEW software. This robot type machine can rescue trapped body from the borehole in a highly secure way